MENINJAU KEMBALI SUMBER LUAR ISLAM DALAM PENAFSIRAN AL-QUR’AN - Yusri Hamzani (UIN Mataram, 2021)
This article discusses the foreign sources of Islam in the interpretation of the Qur'an. There are two main focuses in this article: (1) source forms outside Islam in the interpretation traditions of the Qur'an; (2) Categorization of foreign sources in interpretation traditions. The two main focuses are analyzed using al-dakh?l wa al-'a??l theory which emphasizes the researches of sources in the Book of Tafsir. This type of research is a research library consisting of two sources: primary and secondary. After conducting analysis of such data, the author finds that the source from outside Islam consists of isr??liy?t and Hadith Mau?? ' (false), both of which are categorized as al-Dakh?l bi al-manq?l. In addition to these two, there are also data on science and personal opinions that contradict the values of Qur'anic that became the source of interpretation of the Qur'an, these two things are called al-Dakh?l bi al-Ra'y. Normatively, the two typhology is included in the category al-Dakh?l al-Ma?m?m, the sources that can not be justified when used as a reference in the interpretation and category al-Dakh?l al-Ma?m?d is a reliable source of interpretation.